PERSEPSI MASYARAKAT LOKAL TERHADAP USAHA TANI TANAMAN KARET PADA AREAL BEKAS PERLADANGAN DI DESA NYIIN KECAMATAN JELIMPO KABUPATEN LANDAK - Erwin, Erwin; Zainal, Sofyan; Dirhamsyah, M (Universitas Tanjungpura, 2020)
Rubber gives an important role for the national economy, in West Kalimantan, most of the population work as rubber farmers, especially the community in Nyiin Village, Jelimpo sub-district, Landak district, is one of the villages that runs rubber plantations in the former cultivation area, which has been running since long time ago as the main livelihood to meet the needs of daily life. Some of the problems that are faced by rubber farmers, during the rainy season the rubber farmers have difficulty in tapping rubber, also falling rubber prices nowadays. This affects for the economy and the amount of rubber latex produced by the public. While the prices of basic food are rising, to deal with such a problem the community tends to look for side jobs, such as working in oil palm companies, mining gold, and other jobs. This situation naturally raises perceptions in the local community in Nyiin Village as rubber tappers. The aim of this study to find out the perception of the local community on rubber farming in the former cultivation area and analyze the relationship between knowledge, age and cosmopolitan factors with the perception of the local community on rubber farming in the former cultivation area. This research was carried out for 2 weeks effectively in the field, using descriptive and associative survey methods with interview techniques and questionnaire aids in the form that submitted to a number of respondents. of 81 respondents 73 respondents (90.12%) had low perception, 8 respondents (9.88%) had moderate perception and 0 respondents had low perception of rubber farming. It can be concluded that the people in Nyiin Village, Jelimpo sub-district, Landak district tend to have a low perception of rubber farming, this proves that the community feels the negative impact of the current rubber farming business, caused by the current low price of rubber.Keywords: Communities, Perception, Rubber